Technological Advancement as the Barometer of Death: Syllogistic and Enthymematic Rhetorics as Discursive Seriousness - Yergensen, Brent; Britt, Terry (New Explorations, 2025)
Working to expound upon Braga and Logan’s conception of humor as a device, we explore the intersectionality of humor, death, and differentiation in technological ages. Humor, in a mediated and technological age, informs the rhetoric discipline’s long tradition of honoring significant historical discourses that include legacy orations focused on the delicacy of life, which correlates with this study making the case for a rhetorical function of rhetoric serving the pursuit of survival. As death’s organic response, we argue for a conception of rhetoric that shows its permanent intertwining with life’s end where humor more readily flourishes as part of shared communal discourse, with the case being made in war oratory in early industrial times compared to contemporary, humorous epigrams about death. The rhetorical telling of human history can be understood as a collective effort to escape the inevitability of what is always threatening and always coming: mortality as threatening or as humorous play.